Effect of Curcuma longa on Ovary of Endosulfan Exposed mice - Ranjit Kumar, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Effect of Curcuma longa on Ovary of Endosulfan Exposed mice